The Origin of Harboi in the Light of History. - Baloch, Ghulam Farooq (Al-Burz, 2009)
Few years ago I was thing that Harboi is a specific place in the eastern mountains of Kalat, but after some time it came in my knowledge that the eastern range of mountains which is layout from north to south, called Harboi range of Brahuic range. The word Harboi is an ancient word and it comes in history as it is. According to many people and intellectuals, this is a Persian word, which meaning is every kind good smell, but this meaning never satisfied me, I saw and search the ancient literature about Balochistan, particularly Greek literature of ancient historians, and I successfully achieved my aim. The following article covers the above topic.